Repetitive forging (RF) using inclined punches as a new bulk severe plastic deformation method - Babaei, A.; Faraji, G.; Mashhadi, M.M.; Abd Shukor, Mohd Hamdi (Elsevier, 2012)
A new bulk severe plastic deformation method based on repetitive forging (RF) using inclined punches is proposed. This process consists of two half cycles. In the first half cycle, a square cross section deforms to parallelogram by forging with two inclined punches, and the parallelogram cross section is forged back to square using two flat punches in the second half cycle. This method was applied to commercially pure copper and significant grain refinement was achieved after four passes of RF. The results showed that significant improvement in the mechanical properties was obtained. Notable increase of yield and ultimate strengths corresponding to 358 MPa and 381 MPa after four passes of RF from the initial values of 121 MPa and 230.5 MPa is detectable. Microhardness increases to about 100 Hv after four passes of RF from the initial value of 53 Hv. Finite element (FE) results illustrate that RF is able to impose extremely high plastic strains to the materials. In the RF process, the processed samples have the same dimensions and geometry as those of the initial sample without any waste material and there is no need for back pressure. (C) 2012 Elsevier B.V. All rights reserved.